Bias voltage dependent structure and morphology evolution of magnetron sputtered YSZ thin film: a basic insight. (21st August 2019) - Rusli, N A; Muhammad, R; Ghoshal, S K; Nur, H; Nayan, N; Jaafar, S N
Abstract: YSZ thin films (YSZTFs) with controlled structure and morphology are desirable for low temperature solid oxide fuel cells (SOFCs). We report for the first time the bias voltage (40 V and 120 V) dependent structural and morphological evolution of YSZ thin films grown via radio frequency magnetron sputtering (RFMS) technique. The optimum sample was annealed at 600 °C to achieve an improved ionic conductivity. As-prepared YSZTFs were characterized using various analytical tools. Glancing angle x-ray diffraction (GAXRD) pattern of YSZTFs revealed the existence of non-columnar structure (cubic phases) with preferred growth along [200] lattice orientation. YSZTFs grown at 120 V displayed good homogeneity and uniformity (100 nm thick and crystallite size in the range of 10–12 nm) accompanied by large microstrain along [111] lattice orientation. The bias voltage dependent alterations in the morphology of YSZTFs (grain compactness, size, shape, distribution and surface roughness) were clearly manifested in the FESEM and AFM images. Raman and FTIR spectra of YSZTFs disclosed the formation of tetragonal and cubic phases. An in-depth data analyses suggested the successful incorporation of Yttria into the zirconia lattice. Annealed film exhibited improved polycrystallinity and evolved morphology. These achieved YSZTFs could be effective electrolyte for low temperature SOFC operation.